Spatial Dimensions of Economic Growth, Redistribution, and Poverty Reduction During the Yudhoyono Period in Indonesia - Witri Mukti Aji (Gorontalo State University, 2020)
This research explores the spatial dimensions of economic growth, redistribution, and poverty reduction in Indonesia during the Susilo Bambang Yudhoyono period (i.e., from 2004 to 2014) using the poverty decomposition method, the growth incidence curve, and several pro-poor growth indices. I gathered my data from the annual National Socio-economic Surveys conducted in Indonesia between 2004 and 2014. Analyzing this data, my thesis presents three key economic insights about the Susilo Bambang Yudhoyono period:1) poverty incidence significantly declined between 2004 and 2014, 2) the economic growth that occurred during this period was generally not pro-poor, made evident by an upward sloping growth incidence curve, and 3) regional differences exist in the shape of the growth incidence curve; the pro-poorness of economic growth therefore varies between provinces. Using the classification system proposed by Kakwani and Pernia (2000), I classify provinces into the following five groups with respect to their pro-poor growth index (PPGI). Our empirical results support the pro-poor growth in a nation. However, some provinces such as North Maluku, Gorontalo and Bengkulu experienced non-pro-poor growth and weakly pro-poor. To promote the pro-poor growth in all provinces, the governmental supports in infrastructure and human capital development are essential for the above lagged provinces. Keywords: Household Expenditures; Economic Growth; Redistribution; Poverty Reduction; Spatial Dimensions; Inequality; Poverty Decomposition Method; Growth Incidence Curve; Pro-Poor Growth Indices.